2016
DOI: 10.1111/echo.13375
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic consequences of smoking status in middle‐aged subjects

Abstract: We conclude that currents smokers without known cardiac disease or significant chronic obstructive lung disease show signs of slightly altered hemodynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Increased stroke index was also translated to higher cardiac output in present smokers versus previous smokers. Previously, current smokers had higher cardiac output than never smokers in an ultrasound-based evaluation 18 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Increased stroke index was also translated to higher cardiac output in present smokers versus previous smokers. Previously, current smokers had higher cardiac output than never smokers in an ultrasound-based evaluation 18 .…”
Section: Discussionmentioning
confidence: 98%
“…Some previous reports found that male smokers have increased BP 16 . In contrast, some studies reported that smokers have lower BP than non-smokers 17 , 18 . The putative reduction of BP in smokers may be related to lower body weight, while previous smokers often have higher body weight and increased BP versus never smokers 19 .…”
Section: Introductionmentioning
confidence: 87%
“…However, the present study could not detect the worse effect of smoking exposure against cardiac diastolic function. A previous study also reported an inconclusive association between smoking exposure and cardiac diastolic function owing to the difficulty in obtaining and measuring the data on diastolic function and the effect of other confounding factors [35]. The incomplete measurement of cardiac diastolic function and small sample size might make the results indefinite in the present study.…”
Section: Table 2 Echocardiographic Characteristics Of Participants Acmentioning
confidence: 69%
“…MMP12 is mainly secreted by M2 macrophages (Han et al, 2018;Hotary et al;Lee et al, 2016). Reports have demonstrated that MMP12 can decompose most extracellular matrix and vascular components, and has obvious effects on elastic fiber-rich blood vessels, lung, embryonic development, reproduction, and tissue remodeling (Atlı, 2017;Kraen et al, 2019;Langlois et al;Wagner et al, 2016;Wang et al, 2019;Wetzl et al). MMP12 is associated not only with smoking-induced emphysema (Kraen et al, 2019) but also with the typing of bone marrow cells and myeloid derived suppressor cells (Qu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%